Rationale for recommending a lower dose of primaquine as a Plasmodium falciparum gametocytocide in populations where G6PD deficiency is common - Nicholas J. White (2018)
In areas of low malaria transmission, it is currently recommended that a single dose of primaquine (0.75 mg base/kg; 45 mg adult dose) be added to artemisinin combination treatment (ACT) in acute falciparum malaria to block malaria transmission. Review of studies of transmission-blocking activity based on the infectivity of patients or volunteers to anopheline mosquitoes, and of haemolytic toxicity in glucose 6-dehydrogenase (G6PD) deficient subjects, suggests that a lower primaquine dose (0.25 mg base/kg) would be safer and equally effective. This lower dose could be deployed together with ACTs without G6PD testing wherever use of a specific gametocytocide is indicated. © 2012 White et al.; licensee BioMed Central Ltd.